Segregation patterns of an equidensity TiO2 ternary mixture in a conical fluidized bed: CFD and experimental study - M. rasteh (Iranian Journal of Chemical Engineering)
In this study, an Eulerian-Eulerian multi-fluid model (MFM) was used to simulate the segregation pattern of a conical fluidized bed containing ternary mixtures of equidensity TiO2‌ particles. Experimental 'freeze–sieving' method was employed to determine the axial mass fraction profiles of the different-sized particles, and validate the simulation results. The profiles of mass fraction for large, medium and small sized particles along the bed height during the simulation time indicated that the particles’ segregation can be predicted by CFD model. Effect of superficial gas velocity on segregation pattern was also investigated. It was shown that for U0=1.2Umf, partial segregation of large particles occurred, while for U0=1.6Umf, small and medium size particles also segregated and full segregation was achieved. By increasing U0 to 2Umf, mixing of different sized particles was increased and particles segregation was reduced. Therefore, it can be concluded that there was a critical velocity below which particles would segregate while above which their mixing increased.